Application of Seismic Refraction Tomography in Determining the Soil Hardness Level in IKN Nusantara Area - Alamsyah, Andi; Lepong, Piter; Wahidah, Wahidah; Rahmiati, Rahmiati (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
Numerous studies supporting infrastructure construction are currently underway in the New Capital Territory of Nusantara (IKN Nusantara). A geophysical method known as Seismic Refraction Tomography (SRT) has been employed within the IKN Nusantara to identify hard and soft layers based on the P-wave velocity (Vp). The data acquisition involved 24 channels of geophone spaced at intervals 3 and 4 meters. Measurements were conducted alongfour trajectories of 69 and 92 meters, reaching penetration depths of 12 – 20 meters. P-wave velocity values ranging between 200 – 3500 m/s were recorded. Additionally, the Unconfined Compressive Strength (UCS) value was determined using an empirical equation tailored for mudrock-shale lithology, establishing the correlation between Vp and UCS. In the shallow depths of 0 – 3 meters, UCS values indicated levels below 20 MPa, classifying the materials as having low to medium hardness. However, at depths greater than 3 meters, this layer transitioned to material with high hardness levels, as evidenced by UCS rate exceeding 20 MPa across all trajectories. This suggest that the IKN Nusantara is conducive to infrastructure development.